Nucleosides 8 [18]: Ribosylation of Fused Quinazolines—Synthesis of New [1,2,4]Triazolo[5,1-b]- and [1,2,4]Triazino[3,2-b]quinazoline Nucleosides of Fluorescence Interest - Laila Mohamed Break; Mosselhi Abdelnabi Mosselhi; Nagi Mohamed Elshafai (Journal of Chemistry)
[1,2,4]Triazolo[5,1-b]- and [1,2,4]triazino[3,2-b] quinazolines have been ribosylated by coupling with 1-O-acetyl-2,3,5-tri-O-benzoyl-β-D-ribofuranose and by using the silylation method, followed by debenzoylation by methanolic sodium methoxide to afford the corresponding free N-nucleosides. Nucleosides obtained have been identified by their spectral analysis. From the UV-visible and fluorescence studies of some nucleosides synthesized, it is found that they have fluorescence properties.